Geology, Geochemistry and Hydrothermal Fluid Characteristics of Low Sulfidation Epithermal Deposit in the Sangon Area, Kokap, Special Region of Yogyakarta - Pranayoga Pramumijoyo; Arifudin Idrus; I Wayan Warmada; Kotaro Yonezu (Geological Engineering Department Universitas Gadjah Mada, 2017)
On the basis of the previous studies and reconnaissance survey in the studyarea covering Sangon, Kalirejo, Kokap Sub-district, Kulon Progo Regency, Special Region of Yogyakarta, it reveals some facts of the occurrence of quartz veins with massive, crustiform, comb, drusy cavity, saccharoidal, granular, and reniform/mammillated textures, the appearance of lattice bladed barite and hydrothermal breccia veins. Referring to those characteristics, the deposit type in the study area is interpreted to be low sulfidation epithermal type. This study is aimed to understand and characterize the geological condition, rock and ore geochemistry and the mineralizing fluids. The alteration and ore mineralization are almost observed in entire rock units particularly the intrusive andesite 1. Their formation is controlled by the tension fractures (NW–SE and NE–SW) which associate with sinistral strike slip faults (NE–SW), dilational jog (NNW–SSE), oblique normal fault (WNW–ESE), and predictable normal fault at the NE of study area (NW–SE). The alteration zones are developed to be silica-clay (quartz-illite-kaolinite-kaolinite/smectite), argillic (smectite-illite/smectite), and propylitic (chlorite-calcite±epidote). The precipitationof ore minerals is controlled by boiling, mixing, and wall-rock alteration, and canbe found in the quartz veins (quartz-adularia-sericite) and disseminated in the alteration zones, which their high variability is only can be found in the quartz veins, including pyrite, sphalerite, chalcopyrite, galena, marcasite, and arsenopyrite. Based on the ICPAES measurement of 5 quartz vein samples, the Cu, Zn, Pb, and As grade reach about 5,171 ppm, 8,995 ppm, 6,398 ppm, 34.1 ppm, and 1,010.5 ppm, respectively. Gold is not detected. Fluid inclusion microthermometric analysis shows Th of 242.1–257.6 °C and salinity of 1.57–3.87 wt.% NaCl equiv., which indicate a depth below the paleosurface of 384–516 m, and pressure of 101.7–136.6 bar. The ore deposit in the study area is interpreted to be a deep basemetal low sulfidation epithermal type. Gold might be depleted in this epithermal type.